Fingerprinting and Identification of Bacteria Present in UASB Granules Used to Treat Winery, Brewery, Distillery or Peach-lye Canning Wastewater - Keyser, M.; Britz, T.J.; Witthuhn, R.C. (South African Journal of Enology and Viticulture, 2016)
The effective operation of the anaerobic digestion process in an upflow anaerobic sludge blanket (UASB) bioreactor is dependent on the microbial composition of the UASB granules. The granules contain a consortium of bacteria, with a specific metabolic function for each group, contributing to the overall efficiency and stability of the bioreactor. The aim of this study was to fingerprint and identify the bacteria present in four different types of South African UASB granules that are used to treat winery, brewery, distillery and peach-lye canning wastewaters. This was done by combining conventional microbiological platings with PCR-based denaturing gradient gel electrophoresis (DGGE) and DNA sequence analysis. Each granule type showed distinct PCR-based DGGE fingerprints with unique bands, while other bands were found to be present in all the granules, regardless of the wastewater being treated. Sixty-eight different bacteria (40 pure isolates and 28 clones) were partially sequenced and identified from the winery, brewery, distillery and peach-lye canning granules. Thirty-five percent of the identified bacteria represented the unculturable bacteria and 65% represented the culturable bacteria, which included members of the following genera: Bacillus, Pseudomonas, Bacteroides, Enterococcus, Alcaligenes, Clostridium, Shewanella, Microbacterium, Leuconostoc, Sulfurospirillum, Acidaminococcus, Vibrio, Aeromonas, Nitrospira, Synergistes, Rhodococcus, Rhodocyclus and Syntrophobacter. A DGGE marker was successfully constructed, representing members of the bacterial consortium in UASB granules.